Metastatic pancreatic acinar cell carcinoma in a younger male with marked AFP production: A potential pitfall on fine needle aspiration biopsy. Issue 2 (15th September 2016) - Valente, Kari; Yacoub, George; Cappellari, James O.; Parks, Graham
Abstract : A 30‐year‐old male presented to his doctor with complaints of abdominal pain and was found to have retroperitoneal as well as multiple hepatic masses. A serum alpha‐fetoprotein (AFP) level was significantly elevated (17, 373 ng mL −1 ), raising suspicions for a metastatic germ cell tumor. Fine needle aspiration biopsy of the pancreatic lesion revealed atypical epithelioid cells with round nuclei, large prominent nucleoli, and granular cytoplasm. The morphologic differential diagnosis included pancreatic neoplasm, metastatic germ cell tumor, other metastatic carcinoma, and melanoma. An extensive panel of immunohistochemical stains confirmed the diagnosis of acinar cell carcinoma. The diagnosis of acinar cell carcinoma could be confounded by the markedly increased AFP level, particularly in the setting of a retroperitoneal mass in a younger male. The increased AFP level in the setting of an acinar cell tumor is a potential pitfall to correct diagnosis by cytology. As the treatment for these two entities differs considerably, acute awareness of the phenomenon is important. We present a case of pancreatic ACC with an increased AFP level diagnosed on a cytology specimen. Diagn. Cytopathol. 2017;45:133–136. © 2016 Wiley Periodicals, Inc.